Analysis of BUMDesa Business Development through Business Model Canvas: (Case STUDY on BUMDesa Trasne, Muncan Village, Kopang District, Central Lombok) - Takwani, Baiq Fantri Safarinda; Martiningsih, Rr. Sri Pancawati (Formosa Journal of Applied Sciences, 2024)
Research entitled Analysis of BUMDesa Business Development through Business Model Canvas: (Case Study of BUMDesa Trasne, Muncan Village, Kopang District, Central Lombok) with the aim of analyzing the obstacles faced by BUMDesa Trasne and providing solutions to resolve the obstacles faced by BUMDesa Trasne with the Business Model Canvas concept. The research method used is qualitative with a case study approach. Data collection techniques in this research are through observation, interviews and documentation. The results of this research show that the main obstacles faced are a lack of human resource skills and expertise, inappropriate management decisions, lack of sincerity from management, simple financial reports, government interference, and lack of community support.